Hortifrutícolas orgânicos e agroecologia: conceituação e distribuição comercial - Gaspari, Felipe Campagna de (2013)
This study sought to conceptually discuss organic farming, as part of agroecological science, and to assess its relationship with the current situation of supply of organic fruits and vegetables in different distribution channels in the city of Campinas-SP. The variables considered were price, form of product presentation, variety, packaging types, local production and certification. A comparison was performed with others grocers called "sanitized", "pre-washed", "selected" or "conventional" in this study were grouped under the name of "nonorganic". Ten points of sale was observed, eight hypermarkets, a Organic Fair and a Grocer Street Fair, typical of Brazil. All points are located within a radius of five kilometers from the city center. It was found that, despite the large growth of this market in Brazil, there is still a major bottleneck related to the presentation of products, the understanding of the organic concept, and accessibility to this product by consumers.